The Halal Paradox: Analyzing Price Sensitivity and Actual Purchase Behavior in Indonesia’s Halal Meat Market - Herawati, Mesi; Khusni, Kholilatul (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study examines the